2014
DOI: 10.1371/journal.pone.0097187
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis without Systemic Anticoagulation: A Prospective Randomized Trial to Evaluate 3 Strategies in Patients at Risk of Bleeding

Abstract: ObjectiveIn this clinical trial, we aimed to compare three means of performing chronic hemodialysis in patients with contra-indication to systemic heparinization.MethodsThis open-label monocentric randomized « n-of-one » trial, conducted in a single tertiary care center, recruited chronic hemodialysis patients with a contra-indication to systemic heparinization for at least 3 consecutive sessions. All patients underwent hemodialysis with an AN69ST dialyzer, and were administered three alternative dialysis proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 21 publications
2
39
0
1
Order By: Relevance
“…Furthermore, the surface of the AN69ST membrane can be coated with heparin by priming with saline-containing heparin. As a consequence, the anti-thrombogenicity of the AN69ST membrane exceeds that of the native AN69 membrane and anticoagulant-free hemodialysis using AN69ST membrane has been reported [40,41]. On the other hand, as the sulfonyl groups on the AN69 membrane adsorb nafamostate mesilate, this anticoagulant is not compatible enough with the AN69/ AN69ST membrane [42].…”
Section: Pmma Hemofiltermentioning
confidence: 99%
“…Furthermore, the surface of the AN69ST membrane can be coated with heparin by priming with saline-containing heparin. As a consequence, the anti-thrombogenicity of the AN69ST membrane exceeds that of the native AN69 membrane and anticoagulant-free hemodialysis using AN69ST membrane has been reported [40,41]. On the other hand, as the sulfonyl groups on the AN69 membrane adsorb nafamostate mesilate, this anticoagulant is not compatible enough with the AN69/ AN69ST membrane [42].…”
Section: Pmma Hemofiltermentioning
confidence: 99%
“…A major side effect is the occurrence of bloodline clotting which reduces the delivered dialysis dose and generates blood loss . The additional use of periodic saline rinse have improved ECC survival but it was shown in some studies that it increases coagulation markers and premature restitution frequency . Also, saline flushes if not associated to additional ultrafiltration rate may lead to hypervolemia.…”
Section: Discussionmentioning
confidence: 99%
“…A possible alternative is represented by the use of heparin‐coated membrane, a material that has the ability to bind heparin in its surface providing predominantly a local anticoagulation effect . Results were, however, equivocal; circuit coagulation was reported with a frequency varying from 5 to 50% and early termination of dialysis session from 5% to 7% . We routinely used a modified polyacrylonitrile membrane (AN69ST) for HD sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin-grafted membranes, compared to regular saline flushes, have been shown to be safe and useful method for patients at increased risk of bleeding, such as gastrointestinal bleeds, during invasive procedures, those at perioperative risk, or cerebral hemorrhage [25], [26]. A randomized study that included 48 hemodialyzed patients with a high risk of bleeding found that priming AN69ST with a heparinized saline infusion was more efficient than using an intermittent or continuous saline infusion to prevent blood clotting during HD sessions without anticoagulation [26]. Partial adsorption of heparin from the membrane and incomplete removal of the priming solution before connecting the patient to the extracorporeal circuit occur when using the heparin adsorption protocol, with subsequent systemic anticoagulation caused by circulating heparin.…”
Section: Discussionmentioning
confidence: 99%